中国话语原则 = Principles of Chinese Communication - Xu, Shi (Sinología hispánica. China Studies Review, 2017)
处在不断变化中的中国正吸引着多个学科 和研究视角的关注。从文化意识出发，如何对 中国进行全面而公正的理解是当下学界应当思 考的问题。作者首次从跨文化对话的视角对西 班牙语国家和地区提出了当代中国话语交际的 基本原则。它包括带有中国话语特色的相关概 念、原则、价值观、策略、历史和文化关系。 话语的最重要性质是其文化性：不同话语社群 有着不同的思维方式、观念、看法、交际原则 和策略；他们之间存在着互动、竞争和合作关 系。本文从这样的文化话语视角出发，勾勒出 当代中国的话语特征，并以实际案例说明中国 话语的规律性，为指导中国话语研究、教育与实践提供了启示与借鉴。 The changed and changing China is attracting increasing attention from diverse disciplinary perspectives but a comprehensive, culturally-conscious and so fair understanding has been hard to come by. In this first contribution for the Spanish-speaking community, I outline an account of the general principles underlying contemporary Chinese communication with a view to fostering intercultural dialogue. These take the form of concepts, rules, values, strategies, and historical and cultural relations specific to or characteristic of Chinese discourse. In the process, implications are drawn for correcting universalistic, a-cultural and a-historical conceptions of human communication and for guiding Chinese communication research, education and practice.